The Use of Think-Pair-Square-Share (TPSS) Strategy in Teaching Speaking Recount Text of Seven Course - Muhammad Luthfi; Lailatul Musyarofah; Yudy Prasetyo (PGRI Provinsi Jawa Timur, 2022)
This study aims to descrie the implementation of Think-Pair-Square-Share (TPSS) Strategy in teaching speaking of recount text and the students’ response to the implementation in speaking recount text by using TPSS Strategy. TPSS technique is an effective technique and interesting technique. This research used Qualitative Design with 10 students as the participants. The research instruments were observation checklist, field notes, and questionnaire. The finding of Think-Pair-Square-Share (TPSS) Strategy in teaching speaking recount text were : Firstly, the teacher Explained the recount text, give questions and example of recount text, explain about Think-Pair-Square-Share (TPSS) Strategy, gave stimulus about the material, made five groups. Then, the teacher asked the students to discuss with their group about their maps using TPSS. At last, the students share their story with their group but all the students must tell about their story to all of the groups. The teacher gave feedback, and revied the material to the students. The result showed that the teacher who implements Think-Pair-Square-Share (TPSS) Strartegy in teaching speaking of recount text can make the students are able to speak English fluency. The students enjoy and easily understand the material. In short, the students were motivate in learning speaking English and help them easier to understand the text and material with fun situation